Christian Theology - Judith Wolfe (St Andrews Encyclopaedia of Theology, 2022)
This article introduces Christian theology in its substantial, structural, biblical, historical, and contextual dimensions. Section 1 lays out the substance of theology: after an introductory discussion of the term ‘theology’ and its developing meaning within Christianity, the section introduces theology’s central subjects, outlining their basic claims, their key questions, and the main challenges they face. Section 2 lays out the structure within which this substance takes shape: the principles on whose basis theology treats its subjects, the extent of its capacities to do so, and the settings in which it functions. This section also outlines the organization of theology as an academic discipline. Section 3 discusses the sources of theological content, practice, and imagination in the Bible: the Old Testament, the New Testament, and the Bible as a unified canon. This section also briefly discusses the relationship between theology and modern biblical studies. Section 4 offers a brief overview of the history of theology, enumerating the challenges and achievements, as well as the institutions, forms, and people that enabled them, of the five large periods of Christian history in the West: the Patristic era, the Middle Ages, Reformation and post-Reformation, the Enlightenment, and late modernity. This section also outlines Eastern Orthodox periodizations after the Great Schism of East and West, and the volatile history of Jewish Christianity. Section 5 presents theology as a practice shaped by traditions: denominational traditions, spiritual traditions, and contextual traditions. Section 6 concludes the article with a brief consideration of theology as science and as art, also discussing its critical and constructive relationships to the natural, applied, and social sciences and to the visual, literary, and musical arts.